Proxy-based sliding mode control of a robotic ankle-foot system for post-stroke rehabilitation. (2nd August 2016) - Chen, Geng; Zhou, Zhihao; Vanderborght, Bram; Wang, Ninghua; Wang, Qining
Abstract : Robotic platform-based ankle–foot rehabilitation systems have been proved effective in treating joint spasticity and/or contracture of stroke survivors. However, simple force or velocity limiters are not adequate, since they cannot explicitly guarantee slow and overdamped motions without overshoot. In this paper, we propose a proxy-based sliding mode control (PSMC)-based approach, to avoid unsafe behaviors of a robotic ankle–foot rehabilitation system. The proposed method has three advantages: (1) without deteriorating tracking performance during normal operation, it guarantees overdamped, slow, and safe recoveries after abnormal events; (2) it provides a simple and accurate way to confine the output torque exerted on the subject's ankle; (3) though effective, the control law avoids the necessity to identify the specific system model or build state observer, which is usually difficult for human–robot interaction system. A 71-year-old stroke patient and 10 able-bodied subjects were recruited for the experiments. Preliminary studies comparing PSMC and PID are performed on trajectory tracking, controlled torque output, slow and safe response under disturbance. Additionally, by fulfilling the rehabilitation method and obtaining biomechanical indicators, the proposed controller is proved to be feasible for the system. Graphical Abstract: